Impact of maternal body mass index and gestational weight gain on maternal and neonatal outcomes in twin pregnancies. (21st November 2022) - Schubert, Julia; Timmesfeld, Nina; Noever, Kathrin; Behnam, Susann; Vinturache, Angela; Arabin, Birgit
Abstract: Introduction: To date, there have only been provisional recommendations about the appropriate gestational weight gain in twin pregnancies. This study aimed to contribute evidence to this gap of knowledge. Material and methods: Using a cohort of 10 603 twin pregnancies delivered between 2000 and 2015 in the state of Hessen, Germany, the individual and combined impact of maternal body mass index and gestational weight gain on maternal and neonatal outcomes was analyzed using uni‐ and multivariable logistic regression models. The analysis used newly defined population‐based quartiles of gestational weight gain in women carrying twin pregnancies (Q1: <419.4 g/week [low weight gain], Q2–Q3: 419.4–692.3 g/week [optimal weight gain], Q4: >692.3 g/week [high weight gain]) and the World Health Organization body mass index classification. Results: Pre‐pregnancy body mass index ≥25 kg/m 2 was associated with significantly increased rates of cesarean deliveries (aOR1.2, 95% CI: 1.01–1.41) and pregnancy‐induced hypertensive disorders (aOR 1.53, 95% CI: 1.11–2.1) but not with any adverse neonatal outcome. Perinatal mortality (aOR 2.23, 95% CI: 1.38–3.6), preterm birth (aOR 1.88, 95% CI: 1.58–2.25), APGAR′5 < 7 (aOR 1.61, 95% CI: 1.19–2.17) and admissions to the neonatal intensive care unit (aOR 1.6, CI: 1.38–1.85) were increased among women with low gestational weight gain. Rates of cesarean deliveries were high in both women with low (aOR 1.25, 95% CI: 1.05–1.48) and high gestational weight gain (aOR 1.17, 95% CI: 1.01–1.35). A high gestational weight gain was also associated with higher rates of hypertensive disorders in pregnancy (aOR 2.32, 95% CI: 1.79–3.02) and postpartum hemorrhage (aOR 1.72, 95%CI: 1.12–2.63). The risk of preterm birth, low Apgar scores and NICU admissions showed a converse linear relation with pre‐pregnancy body mass index in women with low gestational weight gain. Conclusions: In twin pregnancies, nonoptimal weekly maternal weight gain seems to be strongly associated with maternal and neonatal adverse outcomes. Since gestational weight gain is a modifiable risk factor, health care providers have the opportunity to counsel pregnant women with twins and target their care accordingly. Additional research to confirm the validity and generalizability of our findings in different populations is warranted. Abstract : In twin pregnancies, maternal gestational weight gain is associated with adverse maternal and neonatal outcomes. High gestational weight gain increased the risk of hypertensive disorders and cesarean deliveries, low gestational weight gain increased the risks of perinatal mortality, preterm birth and cesarean deliveries.